Health assessment of patients over 65 in selected hospital wards - Magdalena Michalczak; Milena Zielonka; Katarzyna Bojarczuk; Agata Barbara Smoleń (Kazimierz Wielki University, 2018)
Introduction: Aging is currently a process that is progressing significantly, in which modern medicine and leading a healthy lifestyle are important factors. Unfortunately, age is most often associated with a deteriorating state of health. The gradual reduction of biological reserves in people over 65 years of age reduces the response to pathogens and triggers the simultaneous occurrence of symptoms characteristic of aging. Objective: Assess the health of patients over 65in selected hospital wards. Materials and methods:The study was conducted among 142 patients over 65 years of age, who were hospitalized in the following wards: Neurology, Rheumatology, Endocrinology and Internal Medicine,atSamodzielnyPublicznySzpitalKliniczny nr 4 w Lublinie[Independent Public Clinical Hospital No. 4 in Lublin] and 1 WojskowySzpitalKliniczny z Polikliniką w Lublinie[Military Clinical Hospital No. 1 with the Polyclinic in Lublin]between December 2015 and May 2016. Results: Better performance is statistically more common for people below 75 years of age, living alone, taking 1-2 medication(s),as well as not having neurological/rheumatic diseases or mental disorders. Lower scores, indicating better functional capacity in each of the areas, were recorded for younger people. Conclusions: 1. Functional capacityin patients over 65 with relation of basic life activities differs significantly. 2. Patients over 65 who are in selected hospital wards are mostly at varied risk of falling and risk of malnutrition. 3. Mental and psychiatric state is normal in most patients over 65 years of age. 4. Patients show reduced functional capacity in all NOSGER areas. 5. Health status in respondents is significantly affected by: old age, systematic intake of 5 and more medications per day, as well as neurological/rheumatic diseases and mental disorders.